A Comparative Study of Using Students Team Achievement Division (STAD) and Three Minutes Review (TMR) Strategies in Teaching Questions - Endah Fauziningrum (Register Journal, 2012)
The objective of this research was to find out the effectiveness of using STAD and TMR strategies to teach questions to the third grade of elementary school students. The data of the research were taken in Sompok state elementary school 03 and 04. The research design used was factorial design. It means that the writer had two groups, one was taught by using STAD strategy and the other was taught by using TMR strategy. STAD and TMR strategies had two sub-divisions, students who take English courses and students who do not take English courses. The number of the research sample for each cell was 12 students. There were four time lesson of periods for STAD and TMR classes. To investigate the effectiveness of using STAD and TMR strategies, the writer used F-test formula. The results were: 1) STAD was effective to teach question to students who take English courses. It was showed from the pre-test (10.83) and the post-test (12.75). 2) STAD was effective to teach question to students who do not take English courses. It was shown on the mean of pre-test (8.58) and the post-test (11.25). 3) TMR was effective to teach question to students who take English courses. It was shown on the mean of pre-test (10.67) and the post-test (11.50).  4) TMR was effective to teach question to students who do not take English courses. It was shown on the mean of pre-test (9.83) and post-test (10.42). There was not any interaction between the students who take English courses and who do not and and who were taught by using STAD and TMR atrategies.it showed from the ANOVA result. The result was the interaction between strategies and taking courses variables showed 0.325 with sig 0.571. Since, sig 0.571 0.05, then the interaction between strategies and taking courses variables do not effect the students achievement. Keywords:  Comparison; Third Grade Elementary School Students; STAD Strategy; TMR Strategy;the Effectiveness of Using Teaching Strategy